Physical activity and obesity - Bouchard, Claude; Katzmarzyk, Peter T. 1968- (Champaign, IL Human Kinetics, 2010)
Physical Activity and Obesity, Second Edition, addresses an array of topics that explore and divulge the links between physical activity (or inactivity) and obesity. Leading scientists from various backgrounds team up to provide an unrivaled resource examining the latest research and developments in the field. Each chapter provides researchers and practitioners with a clear explanation of the concepts, research techniques, and results of studies critical to understanding physical activity and the obesity epidemic. In the 10 years since the first edition of this book was published, the field of physical activity and obesity has mushroomed with new research, sparking the need for not only a new edition but an innovative and refreshing approach to the contents. Editors Bouchard and Katzmarzyk create a go-to resource with 89 succinct, authoritative chapters that may be used independently or as a complete text. Packed with the most up-to-date information linking obesity and physical activity, this comprehensive book: delves into areas of uncertainty and controversy instead of avoiding them or skirting the issues; emphasizes, where appropriate, the underlying mechanisms between physical activity and obesity; and points to research areas that need further exploration and attention. The nine parts of the book flow logically and address obesity in all populations, including children and adults of various backgrounds, ethnicities, and social classes. An overview of the methods used in assessing the levels of sedentary behavior and physical activity is given, followed by a global view of the problem of physical inactivity and obesity. Readers will learn about the key determinants of physical activity levels and obesity and the links between a sedentary lifestyle and the risk of obesity. Other topics examined include behavioral and environmental correlates and determinants of obesity, the relationship between low physical activity energy expenditure and obesity risk, clinical implications, and policy and research issues related to physical activity and obesity. Physical Activity and Obesity, Second Edition, helps readers better understand the role of physical activity in the overall energy balance equation. The unique format, expert contributors, and complete references make this resource indispensable for researchers, health and exercise practitioners, and students studying the ever-expanding topic of obesity as it relates to physical activity.
Part I. Definition and Assessment of Physical Activity and Obesity -- Chapter 1. Introduction / Claude Bouchard and Peter T. Katzmarzyk -- Chapter 2. The Physical Activity and Exercise Continuum / Darren Warburton -- Chapter 3. Assessing the Level of Sedentarism / Mark S. Tremblay -- Chapter 4. Assessing the Level of Physical Activity in Adults / Barbara E. Ainsworth -- Chapter 5. Assessing the Level of Physical Activity in Children / Russell E. Pate -- Chapter 6. Assessment of Obesity in Adults / George A. Bray -- Chapter 7. Assessment of Obesity in Children / John H. Himes -- Chapter 8. The Limitations of Self-Report in Physical Activity and Obesity Research / Richard P. Troiano -- Part II. Prevalence and Cost Issues -- Chapter 9. The Prevalence of Adult Physical Inactivity Around the World / Wendy J. Brown -- Chapter 10. The Prevalence of Childhood Physical Inactivity Around the World / Chris Riddoch -- Chapter 11. The Prevalence of Adult Obesity Around the World / W. Philip T. James -- Chapter 12. The Economic Cost of Obesity / Peter T. Katzmarzyk -- Chapter 13. The Prevalence of Childhood Obesity Around the World / Tim Lobstein -- Chapter 14. The Economic Cost of Physical Inactivity / Ian Janssen -- Chapter 15. The Cost-Benefit Relationship of Physical Activity Interventions for Obesity / Larissa Roux -- Part III. Determinants of Physical Activity Levels -- Chapter 16. Biological Regulation of Physical Activity Level / Catherine M. Kotz -- Chapter 17. Genetics and Physical Activity Level / Tuomo Rankinen -- Chapter 18. Epigenetic or Programming Effects on Physical Activity Level / Mark Vickers -- Chapter 19. Socioeconomic Position and Physical Activity Levels / Lise Gauvin -- Chapter 20. Ethnic Differences in Physical Activity Level / Robert L. Newton, Jr. -- Chapter 21. Psychological Factors and Physical Activity Level / Rod K. Dishman -- Chapter 22. Effects of the Built Environment on Physical Activity Level / James F. Sallis -- Part IV. Physical Activity and Risk of Obesity -- Chapter 23. Sedentary Time and the Risk of Obesity in Adults / Ross Andersen -- Chapter 24. Sedentary Time and the Risk of Obesity in Children / Steven L. Gortmaker -- Chapter 25. Physical Activity Level and the Risk of Obesity in Adults / John M. Jakicic -- Chapter 26. Physical Activity Level and the Risk of Obesity in Children / Margarita S. Treuth -- Chapter 27. Childhood Physical Activity and Risk of Adult Obesity / Robert M. Malina -- Chapter 28. Childhood Obesity and Risk of Adult Obesity / Francois Trudeau -- Chapter 29. Physical Activity and Risk of Obesity in Older People / Wendy M. Kohrt -- Chapter 30. Physical Fitness and Risk of Obesity / Steven N. Blair -- Chapter 31. The Interaction of Diet and Physical Activity on Obesity / Tom Baranowski -- Part V. Physical Activity and Biological Determinants of Obesity -- Chapter 32. Physical Activity Level and Resting Metabolic Rate / Angelo Tremblay -- Chapter 33. Physical Activity Level and Thermic Effect Of Food / Yves Schutz -- Chapter 34. Physical Activity Level and Substrate Oxidation Rates / Steven R. Smith -- Chapter 35. Physical Activity Level and Sympathetic Nervous System Activity / Ian Macdonald -- Chapter 36. Physical Activity Level and Adipose Tissue Biology / Isabelle de Glisezinski -- Chapter 37. Physical Activity Level and Leptin Biology / David J. Dyck -- Chapter 38. Physical Activity Level and Hypothalamic Peptides / Christopher D. Morrison -- Chapter 39. Physical Activity Level and Gut Peptides / Stephen C. Woods -- Chapter 40. Physical Activity Level and Thyroid Hormones / Anthony C. Hackney -- Chapter 41. Physical Activity Level and the HPA Axis / Denis Richard -- Chapter 42. Physical Activity Level and Skeletal Muscle Biology / David A. Hood -- Chapter 43. Postexercise Energy Expenditure / Elizabet Borsheim -- Chapter 44. Genetics of Obesity / Ruth J.F. Loos -- Chapter 45. Epigenetic Effects on Obesity / Peter Nathanielsz -- Part VI. Physical Activity, Behavioral and Environmental Determinants of Obesity -- Chapter 46. Physical Activity Level and Sleep / Shawn D. Youngstedt -- Chapter 47. Physical Activity Level and Occupational Work / David R. Bassett, Jr. -- Chapter 48. Physical Activity Level and Mode of Transportation / Catrine Tudor-Locke -- Chapter 49. Effects of the Built Environment on Obesity / Neville Owen -- Chapter 50. Socioeconomic Status and Obesity / Youfa Wang -- Chapter 51. Physical Activity Level and Dietary Intake / Conrad Earnest -- Part VII. Physical Activity in the Prevention and Treatment of Obesity -- Chapter 52. Physical Activity in the Prevention of Weight Gain / Mikael Fogelholm -- Chapter 53. Physical Activity for Weight Loss / Robert Ross -- Chapter 54. Physical Activity Versus Diet-Induced Weight Loss / Joseph Donnelly -- Chapter 55. Role of Physical Activity in Pharmacological Weight Loss / Frank Greenway -- Chapter 56. Role of Physical Activity in Surgical Weight Loss / Paul O'Brien -- Chapter 57. Physical Activity and Depot-Specific Fat Loss / Victor Katch -- Chapter 58. Physical Activity, Visceral Fat, and Ectopic Fat Deposition / Bret Goodpaster -- Chapter 59. Physical Activity, Weight Loss, and Maintenance of Lean Mass / Steven Heymsfield -- Chapter 60. Physical Activity for Weight Loss Maintenance / Rena Wing -- Chapter 61. Physical Activity and Weight Control During Pregnancy / Michelle Mottola -- Chapter 62. Physical Activity and Postpartum Weight Loss / Cheryl Lovelady -- Chapter 63. Physical Activity and Birth Weight / Johan G. Eriksson -- Chapter 64. Physical Activity and Body Composition in Children / Bob Gutin -- Part VIII. Clinical Implications -- Chapter 65. Physical Activity and Mortality Rates in Obesity / Kevin R. Fontaine -- Chapter 66. Physical Activity and Impaired Glucose Tolerance in Obesity / Markku Laakso -- Chapter 67. Physical Activity and Type 2 Diabetes in Obesity / Edward S. Horton -- Chapter 68. Physical Activity and Hypertension in Obesity / James M. Hagberg -- Chapter 69. Physical Activity and Heart Disease in Obesity / Timothy Church -- Chapter 70. Physical Activity and Stroke in Obesity / Janice Eng -- Chapter 71. Physical Activity and Endothelial Dysfunction in Obesity / Christopher A. DeSouza -- Chapter 72. Physical Activity and Inflammation in Obesity / Mark Hamer -- Chapter 73. Physical Activity and Depression in Obesity / Adrian H. Taylor -- Chapter 74. Physical Activity and Breast Cancer in Obesity / Kerry S. Courneya -- Chapter 75. Physical Activity and Colon Cancer in Obesity / I-Min Lee -- Chapter 76. Physical Activity and Other Cancers in Obesity / Roy Shephard -- Chapter 77. Physical Activity, Obesity, and Metabolic Syndrome / Mercedes R.Carnethon -- Chapter 78. Physical Activity and Musculoskeletal Disorders in Obesity / Jennifer M. Hootman -- Chapter 79. Physical Activity and Risk of Falls in Obese Elderly / Teresa Liu Ambrose -- Chapter 80. Adverse Events of Physical Activity in Obese Persons / Kenneth E. Powell -- Chapter 81. Physical Activity and CVD Risk Profile in Obese Children / Lars Bo Andersen -- Chapter 82. Physical Activity and Risk of Diabetes in Obese Children / Louise Baur -- Part IX. Policy and Research Issues -- Chapter 83. Global Policy Initiatives Related to Physical Activity and Obesity / Timothy Armstrong -- Chapter 84. The Role of Government in the Promotion of Physical Activity / Art Salmon -- Chapter 85. Community-Based Physical Activity Programs to Address Obesity / W. Kerry Mummery -- Chapter 86. School-Based Physical Activity Programs to Address Obesity / Chantal Simon -- Chapter 87. The Role of Industry in the Promotion of Physical Activity / John C. Peters -- Chapter 88. Mass Media Approaches to Addressing Physical Inactivity and Obesity / Adrian Bauman -- Chapter 89. Physical Activity and Obesity Research: Looking to the Future / Peter T. Katzmarzyk and Claude Bouchard.
Includes bibliographical references
Keywords: Obesity; Exercise -- Physiological aspects